1999
DOI: 10.1046/j.1365-2168.1999.01016.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of positron emission tomography with 2-[18F]fluoro-2-deoxy-d-glucose for the differentiation of chronic pancreatitis and pancreatic cancer

Abstract: The results give further evidence that FDG-PET is an important non-invasive method for the differentiation of chronic pancreatitis and pancreatic cancer. Delayed image acquisition in the glycolysis plateau phase permits improved diagnostic performance. This imaging technique is extremely helpful before operation in patients with an otherwise unclear pancreatic mass, despite its costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(42 citation statements)
references
References 18 publications
3
39
0
Order By: Relevance
“…Current image and laboratory tests have improved the diagnostic efficiency to some extent, but insufficiently. Recently, fluorine-18 fluorodeoxyglucose positron emission tomography (FDG-PET) has been widely used for the diagnosis of pancreatic cancer, and is reported to be a valuable diagnostic modality for differentiating malignant from benign lesions of the pancreas 1,2,3,4,5,6,7 . Therefore, many patients who are suspected of having pancreatic cancer tend to undergo FDG-PET, which is necessary to differentiate between pancreatic cancer and benign pancreatic conditions such as tumor-forming chronic pancreatitis.…”
Section: Introductionmentioning
confidence: 99%
“…Current image and laboratory tests have improved the diagnostic efficiency to some extent, but insufficiently. Recently, fluorine-18 fluorodeoxyglucose positron emission tomography (FDG-PET) has been widely used for the diagnosis of pancreatic cancer, and is reported to be a valuable diagnostic modality for differentiating malignant from benign lesions of the pancreas 1,2,3,4,5,6,7 . Therefore, many patients who are suspected of having pancreatic cancer tend to undergo FDG-PET, which is necessary to differentiate between pancreatic cancer and benign pancreatic conditions such as tumor-forming chronic pancreatitis.…”
Section: Introductionmentioning
confidence: 99%
“…Previously published series involving 18-FDG PET in the evaluation of pancreatic adenocarcinoma reported a sensitivity ranging from 82% to 100% and a specificity of 67% to 100%. [25][26][27] Rose et al 19 reported a sensitivity of 92% and a specificity of 85% in detecting pancreatic cancer for 18-FDG PET versus 65% and 62% for CT scanning. However, the role of 18-FDG PET in the evaluation of pancreatic cystic tumors has not been previously investigated.…”
Section: Discussionmentioning
confidence: 99%
“…More detailed analysis of FDG uptake during PET by semi-quantitative techniques may be more accurate for diagnosis, cut-off values have always been calculated retrospectively without prospective evaluation and there is a wide variation in the diagnostic threshold values (table 4) [20, 21, 23, 24, 26, 27, 37]. Indeed it is recognised that a standardised uptake ratio threshold for the differentiation between chronic pancreatitis and pancreatic cancer does not exist [37].…”
Section: Discussionmentioning
confidence: 99%
“…Initial reports that FDG PET was of diagnostic value [21,22,23, 35] were further supported [24,25,26,27,36,37,38,39] to the extent that a consensus conference in Germany concluded that FDG PET had achieved an established clinical role in the diagnosis and staging of pancreatic cancer [40]. More recent studies have however failed to demonstrate any advantage for FDG PET compared to CT [28, 29, 31, 41, 42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation